Conductive polymer coated silicon-carbon composite material as well as preparation method and application thereof
By covering conductive polymers in the porous carbon of the lithium battery negative electrode material and depositing silicon particles, a screen-type structure is constructed, which solves the problem of high expansion rate and many side reactions during the charging and discharging process of the negative electrode material, and achieves high cycle stability, low expansion rate and excellent fast charging performance.
Patent Information
- Application Number
- CN202411806267.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The existing lithium battery negative electrode materials have problems such as high expansion rate, many side reactions and poor rate performance during charging and discharging, which cannot meet the needs of fast charging.
The silicon-carbon composite material coated with conductive polymer is coated with conductive polymer by spray drying, and silicon particles are deposited in vapor deposition method to construct a screened structure to reduce side reactions and expansion rates while improving conductivity and rate performance.
It effectively reduces the volume expansion rate of the negative electrode material, reduces the occurrence of side reactions, improves cycle stability and first-time Coulomb efficiency, and significantly improves the rate performance, which is suitable for fast charging needs.
Smart Images

Figure CN119650636A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery negative electrode materials, in particular to a silicon-carbon composite material coated with a conductive polymer and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have become the mainstream in the market due to their outstanding advantages such as high energy density, high safety and long service life.
[0003] The negative electrode material is one of the core factors affecting the energy density of lithium batteries. The traditional negative electrode material is mainly graphite, whose theoretical specific capacity is about 372mAh / g. The current commercial graphite capacity has reached about 365mAh / g, which is close to its theoretical specific capacity, limiting the further improvement of battery energy density. In order to break through this limitation, researchers began to explore new negative electrode materials such as silicon-carbon negative electrode materials. Silicon-carbon negative electrode materials deposit silicon particles in a porous carbon matrix to construct a nano-silicon-carbon composite structure. However, during the charging and discharging process: (1) The silicon-carbon negative electrode material particles still have an expansion rate of up to 150%, which in turn causes the battery capacity to decay and the service life to be reduced, seriously affecting the battery's cycle performance. (2) The pore structure of the porous carbon matrix is unreasonable, and the electrolyte will enter the pore structure of the porous carbon matrix, causing more side reactions and affecting the electrochemical performance. In addition, the rate performance of this type of negative electrode material is also poor, which cannot meet the current market requirements for fast charging.
[0004] To this end, the present invention is proposed. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a silicon-carbon composite material coated with a conductive polymer and a preparation method and application thereof.
[0006] The present invention is achieved in that:
[0007] First, the present invention provides a silicon-carbon composite material coated with a conductive polymer, comprising: a porous silicon-carbon material and a conductive polymer coated on the surface thereof, wherein the pore width of the porous structure in the conductive polymer-coated silicon-carbon composite material is smaller than the pore width, the porous silicon-carbon material comprises porous carbon and silicon particles deposited in the porous carbon, the conductive polymer comprises a polymer framework and a conductive material distributed in the polymer framework, the conductive material comprises: at least one zero-dimensional conductive substance, at least one one-dimensional conductive substance and at least one two-dimensional conductive substance, and the component content of each conductive substance satisfies formula (1):
[0008]
[0009] Where: m A is the mass percentage of component A in the whole system, P c,Ais the mass fraction percolation threshold of component A in the polymer framework.
[0010] After the conductive polymer is coated, the pore diameter of the porous structure on the porous carbon is reduced, so that the width of each pore is smaller than the width inside the pore, thus constructing a sieving structure that sieving liquid substances. The existence of this sieving structure: (1) In practical applications, only lithium ions are allowed to enter the pores through the pores after desolvation and react electrochemically with silicon particles, while other substances such as electrolyte are not allowed to enter. Therefore, the occurrence of side reactions can be effectively reduced, thereby improving the cycle stability and first coulomb efficiency of the negative electrode material. (2) Buffer space is reserved for the volume expansion of silicon particles during the lithium insertion and extraction process, thereby reducing the volume expansion rate of the negative electrode material.
[0011] The conductive material is composed of at least one zero-dimensional conductive material, at least one one-dimensional conductive material, and at least one two-dimensional conductive material in a specific ratio: (1) The mixture of conductive materials of different dimensions can form a conductive network, thereby improving the overall conductive performance; (2) The mixture of conductive materials of different dimensions can form a more solid and stable structure and disperse stress, thereby improving the overall mechanical properties and anti-destruction ability; (3) Conductive materials of different dimensions can effectively reduce the percolation threshold of the system, improve conductivity, and enhance rate performance.
[0012] The present invention adds conductive materials of various dimensions mixed in a specific ratio into the polymer and coats the conductive polymer on the outside of the porous silicon-carbon material. This not only helps to construct a screening structure, improve the cycle stability and first coulomb efficiency of the negative electrode material, and reduce the volume expansion rate, but also can effectively reduce the percolation threshold of the system, significantly improve the conductivity, and greatly enhance the rate performance, ultimately obtaining a lithium-ion battery negative electrode material with high first efficiency, low expansion, high cycle stability and excellent fast charging performance.
[0013] Furthermore, the diameter of the porous carbon material is 1-20μm, for example, it can be 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, etc.; the porous structure of the porous carbon is nanoscale.
[0014] Furthermore, reflected in the specific surface area, the nitrogen adsorption and desorption specific surface area of the porous carbon is 1500-2500m 2 / g, for example, 1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m2 / g, 2100m 2 / g, 2200m 2 / g, 2300m 2 / g, 2400m 2 / g, 2500m 2 / g, etc., and the nitrogen adsorption and desorption specific surface area of the conductive polymer-coated silicon-carbon composite material is 1-10m 2 / g, for example, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, etc. Obviously, the nitrogen adsorption / desorption specific surface area of the silicon-carbon composite material coated with the conductive polymer is significantly lower than that of the porous carbon not coated with the conductive polymer, which shows that the conductive polymer has been successfully coated on the surface of the porous carbon.
[0015] Furthermore, the mass percentage of the conductive polymer is 2%-50%, for example, it can be 2%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% and the like.
[0016] The flexible polymer framework in the conductive polymer can effectively alleviate the expansion of silicon particles. The conductive material in the conductive polymer can improve the conductivity and enhance the rate performance of the material. By controlling the mass fraction of the conductive polymer, the gram capacity and expansion rate of the silicon-carbon composite material can be taken into account, and finally a lithium-ion battery negative electrode material with high initial efficiency, low expansion, high cycle stability and excellent fast charging performance is obtained.
[0017] Further, the polymer framework comprises one or more of polyvinylidene fluoride and its derivatives, polyacrylic acid and its derivatives, polyvinyl pyrrolidone and its derivatives, polyvinyl chloride, polyvinyl alcohol, polyethylene oxide, polyacrylonitrile, polypyrrole, and chitosan; the zero-dimensional conductive material comprises one or more of conductive carbon black, acetylene black, Ketjen black, copper, silver, gold, or platinum; the one-dimensional conductive material comprises one or more of carbon fiber, multi-walled carbon nanotubes, oligo-walled carbon nanotubes, or single-walled carbon nanotubes; the two-dimensional conductive material comprises one or more of graphene oxide, reduced graphene oxide, or MXenes.
[0018] It should be noted that MXenes can be represented by the chemical formula MXT, where M refers to transition metals such as Ti, Zr, Hf, V, Nb, Ta, Cr, etc., X refers to C or N, and T refers to surface groups such as O, OH, F, NH, etc. MXenes are two-dimensional nanomaterials with high conductivity and hydrophilicity. Specifically, the present invention can use currently commercialized MXenes such as XFK01 titanium carbide (Ti3C2Tx).
[0019] Compared with the prior art, the present invention coats a silicon-carbon composite material with a conductive polymer, and the conductive polymer contains conductive substances of multiple dimensions mixed in a specific proportion, which can effectively reduce the percolation threshold of the system, improve the conductivity, and enhance the rate performance.
[0020] Secondly, the present invention provides a method for preparing a conductive polymer-coated silicon-carbon composite material, comprising the following steps:
[0021] S1. Conductive polymer coating on porous carbon by spray drying
[0022] First, the polymer framework is uniformly dispersed in a solvent to form a polymer solution, then the conductive material is uniformly dispersed in the polymer solution to form a conductive polymer solution, then the porous carbon is uniformly dispersed in the conductive polymer solution to form a porous carbon-conductive polymer dispersion, and finally the porous carbon-conductive polymer dispersion is spray-dried to obtain porous carbon coated with a conductive polymer;
[0023] The polymer solution and the porous carbon satisfy formula (2):
[0024]
[0025] Wherein: η is the viscosity of the polymer solution in Pa·s, c is the mass percentage of the polymer solution, and d is the average pore size of the porous carbon in nm;
[0026] The present invention has been verified through creative labor that: the polymer solution and the porous carbon satisfy the above relationship. Specifically, when the viscosity of the polymer solvent, the mass percentage of the polymer solution and the average pore size of the porous carbon satisfy the above relationship, the polymer can be coated on the surface of the porous carbon, i.e., outside the pores of the porous structure, without entering the interior of the porous carbon. On the one hand, deposition space is reserved for vapor deposition of silicon inside the porous carbon, thereby promoting the smooth deposition of silicon and increasing the silicon content in the composite material. On the other hand, a buffer space is provided for the volume expansion of silicon during use, thereby reducing the volume expansion rate of the negative electrode material.
[0027] S2. Depositing silicon particles in the product obtained in the previous step by vapor deposition
[0028] The product obtained in the previous step is placed in a vapor deposition chamber, heated to a cracking temperature under the protection of an inert gas, and a gaseous silicon source is introduced for vapor deposition to obtain a silicon-carbon composite material coated with a conductive polymer.
[0029] This implementation method: first, a conductive polymer is coated on the outside of porous carbon by spray drying. The spray drying method has fast drying speed, strong adaptability, good controllability and simple operation, and is easy to realize mechanization and automation; then, silicon particles are deposited in the porous structure of the porous carbon coated with the conductive polymer by vapor deposition to obtain a silicon-carbon composite material coated with a conductive polymer. The vapor deposition method is not only environmentally friendly, highly controllable, and highly efficient in production, but also has good product uniformity and stability. In addition, the high temperature environment of vapor deposition can further optimize the porous structure of the porous carbon, enhance its mechanical strength and stability, and promote the interaction between the silicon particles and the porous carbon to form a more stable bond, thereby enhancing the overall strength and durability of the silicon-carbon composite material.
[0030] Furthermore, in step S1, the solvent includes one or more of water, methanol, ethanol, isopropanol, acetone, toluene, N-methylpyrrolidone, N,N-dimethylformamide, petroleum ether, tetrahydrofuran, and carbon tetrachloride.
[0031] Furthermore, in step S2, the gaseous silicon source contains at least one of monosilane and dichlorosilane, the cracking temperature is 400-800°C, and the cracking time is 60-1500 min.
[0032] In this embodiment, the inert gas is a conventional inert gas, such as nitrogen, argon, helium, etc. The gaseous silicon source is at least one of monosilane and dichlorosilane, preferably programmed to a cracking temperature under the protection of an inert gas, and then the gaseous silicon source is introduced and cracked at a constant temperature, the cracking temperature is 400-800°C, preferably 500-600°C, and the cracking time is 60-1500min, preferably 360-1500min. At the above-mentioned cracking temperature and cracking time, the side groups such as alkyl and carboxyl groups in the polymer framework are removed, which not only helps to construct crystalline micro-regions and improve the mechanical properties and ion transport properties of the conductive polymer, but also eliminates the defects of the conductive material, and enhances the van der Waals force between it and the porous carbon, ensuring the close bonding of the conductive polymer coating layer and the porous silicon-carbon material, and improving the stability of the coating layer.
[0033] The present invention combines the spray drying method with the vapor deposition method, and realizes the industrialized production of the silicon-carbon composite material coated with the conductive polymer with simple operation, which has great promotion value.
[0034] Thirdly, the present invention proposes a negative electrode plate, comprising a negative electrode current collector, on which the above-mentioned conductive polymer-coated silicon-carbon composite material is coated.
[0035] The negative electrode current collector used in the negative electrode sheet is a conventional negative electrode current collector in the art, such as copper foil. The conductive polymer-coated silicon-carbon composite material is used as a negative electrode active material, and is mixed with necessary components such as a negative electrode conductive agent and a negative electrode binder to first prepare a negative electrode slurry, and then the negative electrode slurry is coated on the negative electrode current collector to prepare a negative electrode sheet. Further, the above-mentioned necessary components such as negative electrode conductive agent and negative electrode binder are all conventionally selected in the art, and the coating area, coating thickness, coating method, etc. of the negative electrode slurry on the negative electrode current collector all adopt conventional technical means in the art, and those skilled in the art can make a selection based on actual needs.
[0036] Fourthly, the present invention provides a lithium battery, comprising the above-mentioned negative electrode plate. The lithium battery also includes a positive electrode plate, a separator, an electrolyte, etc., which are conventional choices in the art. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 is the XRD pattern of the product obtained in Example 1;
[0039] Figure 2 TEM image of the product obtained in Example 1;
[0040] Figure 3 1 are nitrogen adsorption-desorption curves of porous carbon, the intermediate product of Example 1, and the intermediate product of Comparative Example 4;
[0041] Figure 4 Small-angle X-ray scattering diagrams of porous carbon, the intermediate product of Example 1, and the intermediate product of Comparative Example 4. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of this application. The operations not described in detail in the following embodiments and comparative examples are all conventional technical means in this field.
[0043] All raw materials involved in the following examples and comparative examples that are not explicitly described are conventional raw materials in the art and can be commercially obtained in the prior art.
[0044] Example 1
[0045] The conductive polymer-coated silicon-carbon composite material was prepared as follows:
[0046] (1) Coating the conductive polymer on the porous silicon carbon material by spray drying
[0047] 20 g of polyacrylic acid (PAA, commercially available, molecular weight 450000) was added to 6 kg of water and dispersed with a homogenizer for 1 hour to obtain a polyacrylic acid polymer solution, and the viscosity of the polymer solution was measured and recorded using a viscometer; 0.005 kg of conductive carbon black (SP), 1.25 kg of carbon nanotube dispersion (SWCNT, commercially available, 0.4 wt%), and 0.005 kg of reduced graphene oxide (rGO) were slowly added to the polyacrylic acid polymer solution, and dispersed with a homogenizer for 1 hour to obtain a conductive polymer dispersion; 1 kg of porous carbon raw material (commercially available, D50 is 8.2 μm, specific surface area is 1953 m 2 / g, pore diameter of 1.85 nm) and dispersed with a homogenizer for 2 hours to obtain a porous carbon-conductive polymer dispersion; the obtained dispersion was dried using a spray drying device at a drying temperature of 160° C. to obtain an intermediate product;
[0048] (2) Depositing silicon particles in the product obtained in the previous step by vapor deposition
[0049] The intermediate product obtained in the previous step was placed in a rotary furnace, and the furnace temperature was raised to 500°C at a heating rate of 10°C / min under argon protection, and then monosilane was introduced with a monosilane flow rate of 2000sccm. After maintaining for 1000min, the introduction of monosilane was stopped to obtain the final product.
[0050] Depend on Figure 1 It can be seen that there is no obvious crystalline silicon peak in the XRD diagram, indicating that the silicon in the product obtained in Example 1 exists in an amorphous form, which is in line with expectations.
[0051] Depend on Figure 2 It can be seen that the conductive polymer-coated silicon-carbon composite material obtained in Example 1 has a layer of polymer uniformly coated on its surface, and a two-dimensional conductive material (yellow dotted line portion) can be seen in the polymer layer, and it is obvious that the conductive polymer has been successfully coated. Moreover, no lattice structure is found in the core material porous silicon carbon, which further indicates that the silicon and carbon matrix exist in an amorphous form.
[0052] In addition, AFM was used to test the force-distance curves of the intermediate product conductive polymer-coated porous carbon and the final product conductive polymer-coated silicon-carbon composite material, and the Sneddon model was used to fit the surface Young's modulus of the two materials. The Young's modulus of the intermediate product conductive polymer-coated porous carbon was 2.73GPa, while the Young's modulus of the final product conductive polymer-coated silicon-carbon composite material was 35.2GPa, indicating that the heat treatment during vapor deposition did effectively improve the mechanical properties of the conductive polymer.
[0053] Depend on Figure 3 As shown: Before coating, the specific surface area of porous carbon is 2059m 2 / g; after being coated with conductive polymer, the specific surface area of porous carbon is 1.8469m 2 / g. Obviously, the conductive polymer has been successfully coated on the surface of porous carbon and effectively covered the pores on its surface.
[0054] Depend on Figure 4 As shown: before and after coating, the internal specific surface area of porous carbon is 2148m 2 / g, 2091m 2 / g. It can be seen that the pore structure of the porous carbon has not been significantly reduced due to polymer coating. Combined with the nitrogen adsorption-desorption curve, it can be determined that a screening structure has been constructed.
[0055] Example 2
[0056] Compared with Example 1, the mass of the polyacrylic acid in step (1) was adjusted to 10 g. The rest was the same as in Example 1.
[0057] Example 3
[0058] Compared with Example 1, the mass of the polyacrylic acid in step (1) was adjusted to 40 g. The rest was the same as in Example 1.
[0059] Example 4
[0060] Compared with Example 1, the mass of the conductive carbon black in step (1) was adjusted to 0.015 kg, and the rest was consistent with Example 1.
[0061] Example 5
[0062] Compared with Example 1, the polyacrylic acid in step (1) is adjusted to a molecular weight of 500,000 and an equal mass of polyacrylonitrile, and the water in step (1) is replaced by an equal mass of N,N-dimethylformamide. The rest is the same as in Example 1.
[0063] Example 6
[0064] Compared with Example 1, the polyacrylic acid in step (1) is adjusted to a molecular weight of 150,000 and an equal mass of polyacrylonitrile, and the water in step (1) is replaced by an equal mass of N,N-dimethylformamide. The rest is the same as in Example 1.
[0065] It should be noted that the XRD patterns and TEM patterns of the final products obtained in Examples 2 to 6 are basically similar to those in Example 1. Further tests show that the nitrogen adsorption-desorption curves and small-angle X-ray scattering of each are also basically similar, so they are not attached separately.
[0066] Comparative Example 1
[0067] Compared with Example 1, only 0.015 kg of SP was added in step (1), and no carbon nanotube dispersion and rGO were added. The rest were the same as in Example 1.
[0068] Comparative Example 2
[0069] Compared with Example 1, in step (1), rGO was not added, but 0.0075 kg SP and 1.875 kg carbon nanotube dispersion were added. The rest was the same as in Example 1.
[0070] Comparative Example 3
[0071] Compared with Example 1, the polyacrylic acid in step (1) was replaced by an equal mass of polyacrylonitrile (PAN, commercially available, molecular weight 450000), and the water in step (1) was replaced by an equal mass of N,N-dimethylformamide. The rest was the same as in Example 1.
[0072] Comparative Example 4
[0073] Compared with Example 1, the polyacrylic acid in step (1) was adjusted to polyacrylic acid with a molecular weight of 100,000. The rest was the same as Example 1.
[0074] Depend on Figure 3 As shown: Before coating, the specific surface area of porous carbon is 2059m 2 / g; after being coated with conductive polymer, the specific surface area of porous carbon is 3.654m 2 / g. Obviously, the conductive polymer has been successfully coated on the surface of porous carbon and effectively covered the pores on its surface.
[0075] Depend on Figure 4 As shown: before and after coating, the internal specific surface area of porous carbon is 2148m 2 / g, 51.18m 2 / g. Obviously, after polymer coating, the pore structure of the porous carbon is significantly blocked. Combined with the nitrogen adsorption-desorption curve, it can be determined that the polyacrylic acid with a molecular weight of 100,000 used in Comparative Example 4 enters the pore structure in large quantities during coating, resulting in the inability to construct a sieving structure.
[0076] Comparative Example 5
[0077] Compared with Example 1, the polyacrylic acid in step (1) is adjusted to a molecular weight of 85,000 and an equal mass of polyacrylonitrile, and the water in step (1) is replaced by an equal mass of N,N-dimethylformamide. The rest is the same as in Example 1.
[0078] The products obtained in each embodiment and comparative example were assembled into button batteries according to the following operations and relevant electrochemical performance tests were performed:
[0079] (1) Preparation of negative electrode sheets: First, the product, negative electrode conductive agent carbon black, and negative electrode binder (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) were mixed and slurried in a mass ratio of 95:2:3 to prepare negative electrode slurry, and then the negative electrode slurry was evenly coated on copper foil, and then dried in a forced air drying oven at 50°C for 2 hours and cut into 8 cm×8 cm electrode sheets, and the electrode sheets were rolled to a compaction density of 0.8 g / cm 3 Then place it in a vacuum drying oven at 100°C for 10 hours and finally punch it into diameters. The negative electrode plate is then transferred into the glove box for standby use.
[0080] (2) Assembling button cells: In a glove box containing a high-purity Ar atmosphere, metallic lithium was used as the counter electrode, 1 M LiPF6 solution (a mixture of EC:DMC in a volume ratio of 1:1 with 10 vol% FEC and 1 vol% VC added) was used as the electrolyte, and polyethylene was used as the separator to assemble button cells for testing.
[0081] (3) Electrochemical performance test: A constant current charge and discharge mode test was performed using a charge and discharge instrument, with a discharge cut-off voltage of 0.005 V and a charge cut-off voltage of 1.5 V. The charge and discharge test was performed twice at a current density of C / 10, 10 times at 0.5C, and 5 times at 2C. Subsequent cycles were performed at 0.5C. The reversible specific capacity, first coulomb efficiency, and full lithium expansion rate of the button battery were tested, and the capacity retention rate after 300 cycles and the high current capacity retention rate were calculated.
[0082] For the convenience of listing, Example 1, Example 2, ... are numbered as S1, S2, ... respectively, and Comparative Example 1, Comparative Example 2, ... are numbered as D1, D2, ... respectively.
[0083] S1, S2, S3, S4, D1, D2, and D3 are listed in Table 1 and compared to explore the effects of different conductive materials, addition amounts, and percolation thresholds on the overall conductivity.
[0084] Table 1 Important technical parameters of some embodiments and comparative examples
[0085]
[0086] It should be noted that: c,A Through experimental measurement, it was found that the test method is a conventional test means in this field. The specific operation is: gradiently add different amounts of specified conductive substances to the specified polymer system, then cast the polymer, and then use four probes to test the conductivity of the system, and then draw the curve and determine the threshold.
[0087] S1, S5, S6, D3, D4, and D5 are listed in Table 2 to explore the effects of polymer type and concentration on the silicon content in the final product.
[0088] Table 2 Effect of polymer type, concentration, etc. on silicon content in the final product
[0089]
[0090] The electrochemical performance test results of various embodiments and comparative examples are shown in Table 3.
[0091] Table 3 Electrochemical performance of each embodiment and comparative example
[0092]
[0093] From Table 1, Table 2, Table 3 and Figure 1-Figure 4 Commonly shown:
[0094] (1) Comparing the conductive materials and test results of S1, S2, S3, S4, D1, D2, and D3, we can know that: If the value is greater than 1, such as S1, S2, S3, and S4 are 1.058, 1.058, 1.058, and 1.415 respectively, then on the basis of maintaining a relatively high first coulombic efficiency and a capacity retention rate after 300 cycles, it also has a large current capacity retention rate of at least 69%, and the rate performance is good; if the value is less than 1, such as D1, D2, and D3 are 0.536, 0.962, and 0.695 respectively, the corresponding large current capacity retention rates are 36.2%, 45.2%, and 50.4% respectively. Obviously, the lower the calculated value, the lower the large current capacity retention rate and the worse the rate performance. At the same time, comparing S4 with S1, S2, and S3, it can be seen that The calculated value of is greater than or equal to 1. On this basis, if more conductive materials are added, the overall conductivity of the silicon-carbon composite material will not be greatly affected, so the improvement of the capacity retention rate of large current is not obvious. The introduction of formula (1) helps to obtain better performance at a lower cost, which is of great guiding significance.
[0095] Obviously, only by adding a mixture of zero-dimensional, one-dimensional, and two-dimensional conductive materials can the percolation threshold of the corresponding polymer system be broken, the conductivity of the polymer coating layer can be greatly enhanced, the problem of poor intrinsic electronic conductivity of the polymer can be solved, and the rate performance of the material can be improved. However, only adding zero-dimensional and / or one-dimensional conductive materials will result in poor conductivity and cannot effectively improve the rate performance of the material.
[0096] (2) Comparing the preparation conditions and test results of S1, S5, S6, D3, D4, and D5, we can see that: If this value is greater than the average pore size d of porous carbon, a relatively high silicon deposition amount can be obtained, and then a better cycle performance can be obtained. For example, the calculated values of S1, D3, S5, and S6 are greater than the average pore size d, which are 6.43, 2.87, 12.13, and 2.03, respectively, and the corresponding silicon contents are 50.8%, 45.9%, 54.4%, and 52.7%; while the calculated values of D4 and D5 are 1.54 and 1.79, respectively, which are both less than the average pore size d, and the corresponding silicon contents are lower, which are 32.1% and 39.2%, respectively. The reason is that when the viscosity of the polymer solvent, the mass percentage of the polymer solution and the average pore size of the porous carbon satisfy formula (2), the polymer can be coated on the surface of the porous carbon, i.e., outside the pores of the porous structure, without entering the porous carbon. On the one hand, it reserves deposition space for the vapor deposition of silicon inside the porous carbon, thereby promoting the smooth deposition of silicon, increasing the silicon content in the composite material, and obtaining good cycle performance. On the other hand, it provides a buffer space for the volume expansion of silicon during use, thereby reducing the volume expansion rate of the negative electrode material. When the calculated value is less than the average pore size d, as shown in D4 and D5, the polymer enters the pores of the porous carbon during coating and blocks the pores, resulting in the inability of silicon particles to be smoothly deposited in the pores of the porous carbon but mainly deposited on the surface of the porous carbon, which not only affects the construction of the sieving structure, but also the silicon particles deposited on the surface are in direct contact with the electrolyte, resulting in a significant increase in the expansion rate of the electrode and serious deterioration of the cycle performance. In summary: the present invention flexibly adjusts the molecular weight, addition amount and solvent type of the polymer to control the viscosity and mass fraction of the polymer solution, and then stably coats the polymer on the porous carbon surface so that it does not enter the pores of the porous carbon, reserving space for the deposition of silicon and volume expansion during use, thereby constructing a sieving structure that does not allow electrolyte to enter; at the same time, a conductive material composed of a mixture of conductive substances of multiple dimensions in a specific proportion is added to the polymer, which can effectively reduce the percolation threshold of the system, significantly improve the conductivity, and greatly enhance the rate performance; under the synergistic effect, the present invention obtains a silicon-carbon composite material coated with a conductive polymer with excellent performance, which can be used as a negative electrode material for lithium-ion batteries, and is helpful to prepare lithium-ion batteries with high initial efficiency, low expansion rate, high cycle stability and excellent fast charging performance.
[0097] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A silicon-carbon composite material coated with a conductive polymer, characterized in that: include: A porous silicon-carbon material and a conductive polymer coated on the surface thereof, wherein the pore width of the porous structure in the conductive polymer-coated silicon-carbon composite material is smaller than the pore width, the porous silicon-carbon material comprises porous carbon and silicon particles deposited in the porous carbon, the conductive polymer comprises a polymer framework and a conductive material distributed in the polymer framework, the conductive material comprises: at least one zero-dimensional conductive substance, at least one one-dimensional conductive substance and at least one two-dimensional conductive substance, and the component content of each conductive substance satisfies formula (1): Where: m A is the mass percentage of component A in the whole system, P c,A is the mass fraction percolation threshold of component A in the polymer framework.
2. The conductive polymer-coated silicon-carbon composite material according to claim 1, characterized in that: The diameter of the porous carbon material is 1-20 μm, and the porous structure of the porous carbon is nanoscale.
3. The conductive polymer-coated silicon-carbon composite material according to claim 1, characterized in that: The nitrogen adsorption and desorption specific surface area of the porous carbon is 1500-2500m 2 / g, the nitrogen adsorption and desorption specific surface area of the conductive polymer-coated silicon-carbon composite material is 1-10m 2 / g.
4. The conductive polymer-coated silicon-carbon composite material according to claim 1, characterized in that: The mass percentage of the conductive polymer is 2%-50%.
5. The conductive polymer-coated silicon-carbon composite material according to any one of claims 1 to 4, characterized in that: The polymer framework comprises one or more of polyvinylidene fluoride and its derivatives, polyacrylic acid and its derivatives, polyvinyl pyrrolidone and its derivatives, polyvinyl chloride, polyvinyl alcohol, polyethylene oxide, polyacrylonitrile, polypyrrole, and chitosan; The zero-dimensional conductive material comprises one or more of conductive carbon black, acetylene black, Ketjen black, copper, silver, gold or platinum; The one-dimensional conductive material comprises one or more of carbon fiber, multi-walled carbon nanotube, few-walled carbon nanotube or single-walled carbon nanotube; The two-dimensional conductive material includes one or more of graphene oxide, reduced graphene oxide or MXenes.
6. A method for preparing a silicon-carbon composite material coated with a conductive polymer as claimed in any one of claims 1 to 5, characterized in that: The steps are as follows: S1. Conductive polymer coating on porous carbon by spray drying First, the polymer framework is uniformly dispersed in a solvent to form a polymer solution, then the conductive material is uniformly dispersed in the polymer solution to form a conductive polymer solution, then the porous carbon is uniformly dispersed in the conductive polymer solution to form a porous carbon-conductive polymer dispersion, and finally the porous carbon-conductive polymer dispersion is spray-dried; The polymer solution and the porous carbon satisfy formula (2): Wherein: η is the viscosity of the polymer solution in Pa·s, c is the mass percentage of the polymer solution, and d is the average pore size of the porous carbon in nm; S2. Depositing silicon particles in the product obtained in the previous step by vapor deposition The product obtained in the previous step is placed in a vapor deposition chamber, heated to the cracking temperature under the protection of an inert gas, and a gaseous silicon source is introduced for vapor deposition.
7. The preparation method according to claim 6, characterized in that: In step S1, the solvent includes one or more of water, methanol, ethanol, isopropanol, acetone, toluene, N-methylpyrrolidone, N,N-dimethylformamide, petroleum ether, tetrahydrofuran, and carbon tetrachloride.
8. The preparation method according to claim 6, characterized in that: In step S2, the gaseous silicon source contains at least one of monosilane and dichlorosilane, the cracking temperature is 400-800°C, and the cracking time is 60-1500 min.
9. A negative electrode sheet, comprising a negative electrode current collector, characterized in that: The negative electrode current collector is coated with the conductive polymer-coated silicon-carbon composite material as described in any one of claims 1 to 5 or the conductive polymer-coated silicon-carbon composite material prepared by the preparation method as described in any one of claims 6 to 8.
10. A lithium battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.
Citation Information
Cited By
Conductive polymer modified porous silicon carbon negative electrode material, negative electrode plate, all-solid-state battery and preparation method of all-solid-state battery
CN121237843A
Silicon-carbon composite material, preparation method thereof, negative plate and battery
CN121260773A
Synergistic modified silicon-carbon negative electrode material, preparation method thereof, negative electrode and battery
CN122246113A
Synergistically modified silicon-carbon negative electrode material, preparation method thereof, negative electrode and battery
CN122246113B